Positive Blood Culture as a Marker of Sepsis and MODS Risk in Critically Ill Children A Narrative Literature Review - Rafly Bayu Surya Wardhana; Arina Setyaningtyas; Rebekah Juniati Setiabudi; Neurinda Permata Kusumastuti (Universitas Mohammad Husni Thamrin, 2025)
Blood culture is an essential examination for establishing the diagnosis of bloodstream infection (BSI) in critically ill children, as it enables the detection of causative pathogens and guides appropriate antimicrobial therapy. This study aims to examine the association between positive blood culture results and disease severity in children admitted to the pediatric intensive care unit (PICU). A literature review was conducted by searching articles in PubMed, Google Scholar, NCBI, and ScienceDirect over the past 15 years, which were then selected based on topic relevance and methodological quality. Analysis of ten studies revealed that positive blood cultures were strongly associated with increased mortality, longer hospital stay, and a higher incidence of multiple organ dysfunction. Frequently reported risk factors included younger age, the use of central venous catheters, immunocompromised conditions, and infections caused by drug-resistant Gram-negative bacteria. Parameters such as time to positivity (TTP), procalcitonin levels, and organ dysfunction scores (PELOD-2) were identified as important prognostic indicators reflecting infection severity. Thus, a positive blood culture serves not only as a diagnostic tool but also as a crucial prognostic marker for risk stratification and clinical decision-making in critically ill children.